Factors Influencing Stillbirths in the West Gonja Hospital of Northern Region - Assunta, Z.M. (University of Ghana, 2017)
Background: Stillbirth remains a public health issue of global concern particularly in developing countries like Ghana. Stillbirth rates continue to remain high in West Gonja Hospital Damongo though preventable. However, the factors influencing stillbirths in the hospital remain unknown. The purpose of this study was to determine the factors influencing stillbirths in the hospital. Specifically, the study determined the proportion of stillbirth, assessed the health facility and obstetric factors associated with stillbirths. Methods: A retrospective analysis of secondary data from delivery registers of the hospital was carried out. All 893 deliveries that met the inclusion criteria from I" January to 31 51 December 2015, were extracted using a data extraction tool adapted from UNICEF. Statistical analysis was done using Stata version 14.1 software. Chi square test, simple and multiple logistics regression were performed. Results: The hospital based stillbirth rate was 23.5/1,000 total births. The odds of stillbirths were higher among low birth weight babies (p < 0.001) compared to normal birth weight babies. Referred cases had high odds of stillbirths (p = 0.001). Foetal distress (p < 0.001) and APH (p = 0.002) were significantly associated with high odds of stillbirths. Stillbirths were more likely to occur among mothers who had inadequate ANC visits at the facility, mothers who received inadequate doses of malaria prophylaxis and among labour cases that were not monitored using the partograph. Conclusion: Stillbirth rate was unacceptably high in the West Gonja Hospital. The study found that stillbirths were associated with low birth weight and referred cases had high odds of stillbirth. The observation highlights the significant contribution of obstetric complications, foetal distress and APH to stillbirths.
MPH
Keywords: Stillbirth; West Gonja; Northern Region; Ghana; Maternal Health; Child birth